1988
DOI: 10.1007/bf00156676
|View full text |Cite
|
Sign up to set email alerts
|

Microtasking general purpose partial differential equation software on the CRAY X-MP

Abstract: Microtasking on four-processor CRAY X-MP computers is examined. The examination includes descriptions of important properties of Cray microtasking and an explanation of how to apply it to a program package. The experience of applying Cray microtasking to the general purpose partial differential equation package PLTMG of R. Bank et al. [1985, 1986] is communicated. Results of experiments in a single-job (dedicated) computing environment show that a large part ofPLTMG's interprocedural parallelism can be exploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Results of microtasking were first reported by Misegades et al [1987], who reported speedups of 3.40 and 3.65 on the CRAY X-MP/4 for two CFD codes. Bieterman [1987] reported speedups of 1.22 to 2.36 on the CRAY X-MP/4 using microtasking for the partial differential equation package PLTMG. On the CRAY-2, Swisshelm [1988] reported a speedup of 2.67 using macrotasking for a three-dimensional Navier-Stokes algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Results of microtasking were first reported by Misegades et al [1987], who reported speedups of 3.40 and 3.65 on the CRAY X-MP/4 for two CFD codes. Bieterman [1987] reported speedups of 1.22 to 2.36 on the CRAY X-MP/4 using microtasking for the partial differential equation package PLTMG. On the CRAY-2, Swisshelm [1988] reported a speedup of 2.67 using macrotasking for a three-dimensional Navier-Stokes algorithm.…”
Section: Introductionmentioning
confidence: 99%